THE ROLE OF SPATIAL MENTAL MODELS IN THE LITERARY COMPREHENSION - Alfaro Vargas, Roy (2013)
This article analyzes the relation existing between time and space, in the conformation of spatial mental models. Besides, it criticizes the cognitive proposal developed by the cognitive psychology. Also, it sets up a relation between the mental models and the Stephen Hawking´s physical conceptions in a dialectical perspective so that it defines the time-spatial mental models concept.